Health-demand ventilation control strategy in northern Chinese homes: how much ventilation do we need to protect occupants’ health - Wang, Zhigang; Hou, Jing; Fu, Jinming; Tian, Zhe; Feng, Shuyuan; Kosonen, Risto; Sun, Yuexia (Frontiers in Built Environment, 2025)
IntroductionIndoor air quality in dwellings has particular importance regarding occupants’ health. Ventilation is an important means to improve indoor air quality and guarantee occupants’ health.MethodsWe utilized CO2 produced by occupants to measure air exchange rate (i.e., the volumetric out-to-indoor airflow rate divided by building volume, h−1) in Chinese homes, which were then linked to health outcomes like asthma and sick building syndrome symptom. Finally, we proposed a “health-demand” ventilation control strategy according to the relationship between air exchange rate and health outcomes.Results and DiscussionEach 0.1 h−1 increase in air exchange rate at night was associated with adjusted odds ratios of 0.97 (Confidence Interval (CI): 0.94–1.00) for rhinitis among children and 0.95 (95% CI: 0.91–0.98) for mucosal sick building symptom among adults. Finally, we proposed a “health-demand” ventilation control strategy according to the relationship between air exchange rate and health outcomes. Air exchange rate of 2.5 h−1 and 6.5 h−1 was suggested to deal with sick building syndrome symptoms among adults and rhinitis symptoms among children, respectively.